Engaging the neighbours. Australia and ASEAN since 1974 - Frost, Frank (ANU Press, 2016)
From modest beginnings in 1967, the Association of Southeast Asian Nations (ASEAN) has become the premier regional institution in Southeast Asia. The 10 members are pursuing cooperation to develop the 'ASEAN Community' and also sponsor wider dialogues that involve the major powers. Australia has been interested in ASEAN since its inauguration and was the first country to establish a multilateral link with the Association, in 1974. Australia and ASEAN have subsequently engaged and cooperated on many issues of mutual concern, including efforts to secure an agreement to resolve the Cambodia conflict (signed in 1991), the initiation of the Asia-Pacific Economic Cooperation grouping (1989) and the ASEAN Regional Forum (1994), the conclusion of the ASEAN-Australia-New Zealand Free Trade Agreement (signed in 2008) and the development of the East Asia Summit (from 2005). This book provides the first available detailed history of the evolution of Australia's interactions with ASEAN. It assesses the origins and phases of development of Australia's relations with ASEAN; the role ASEAN has played in Australian foreign policy since the 1970s; the ways in which the two sides have collaborated, and at times disagreed, in the pursuit of regional stability and security; and the key factors that will influence the relationship as it moves into its fifth decade.